Rancang Bangun Alat Monitoring Pelampung Suar Berbasis Internet of Things (IoT) Terhadap Sarana Bantu Navigasi Pelayaran di Distrik Navigasi Tanjung Perak Surabaya - Djaka Dewa Soekarno; Rizqi Aini Rakhman; Teguh Pribadi; Romanda Annas Amrullah (Pusat riset dan Inovasi Nasional, 2025)
This research discusses issues related to the Navigation Aids, particularly the buoy objects. The study aims to design and develop a monitoring device for buoys based on the Internet of Things (IoT). This study aims to design and develop a buoy monitoring device based on the Internet of Things (IoT) as a solution to the lack of monitoring and supervision of buoys in the Tanjung Perak Navigation District. The identified contributing factors include: (1) displacement of buoys due to ocean currents, (2) suboptimal performance of the flasher lights, and (3) disappearance of the buoys. Using the Research and Development (R&D) method, the researcher designed a monitoring system capable of real-time observation through internet connectivity. The product feasibility test conducted by experts resulted in an average percentage index of 94%, placing it in the 'Highly Feasible' category for use. The results demonstrate that the IoT-based buoy monitoring device significantly enhances the efficiency and effectiveness of buoy supervision. This research is expected to contribute to the development of knowledge within the Bachelor of Applied Science in Marine Transportation program and provide technological innovation in the field of maritime navigation in Indonesia.